EDD 712: Applied Qualitative Research Methods
In this course, students learn the characteristics of various qualitative research traditions, including case study, phenomenology, narrative inquiry, ethnography, grounded theory, and participatory action research. Students explore major paradigms that inform many qualitative research traditions and their implications for the conduct of qualitative inquiry, specifically addressing the various approaches and assumptions about reality, knowledge, and values.